On n-polynomial p-convex functions and some related inequalities - Choonkil Park; Yu-Ming Chu; Muhammad Shoaib Saleem; Nazia Jahangir; Nasir Rehman (Advances in Difference Equations, 2020)
Abstract In this paper, we introduce a new class of convex functions, so-called n-polynomial p-convex functions. We discuss some algebraic properties and present Hermite–Hadamard type inequalities for this generalization. Moreover, we establish some refinements of Hermite–Hadamard type inequalities for this new class.